Dinâmica fitogeográfica e suscetibilidade à desertificação no município de Poço Redondo - SE - Gois, Douglas Vieira (2016)
Historically, Brazil’s semi-arid climate has always suffered an excessive exploitation of natural resources. In this context, combined with the predatory activities carried out on the fragile environmental scenario of this region, a degradation process surges in great intensity, denominated desertification. The aforementioned process consists of the land degradation of arid, semi-arid and sub-humid areas due to several factors, including climate variations and anthropogenic derivations, resulting in negative impacts to both the environment and the affected population. According to the Program of State Action of Combat to Desertification – (PAE-SERGIPE), in the state of Sergipe, the territory Alto Sertão Sergipano is an area affected by the processes of desertification, with a high risk of degradation. However, such statement was not accompanied by detailed studies for the analysis of several different levels of fragility inside the territory. In this sense, this study aimed to analyze the levels of susceptibility to desertification correlated to geoenvironmental indicators (vegetation index (NDVI), soil types, relief, pluviosity and land use), with emphasis on the dynamic vegetation cover, during the time period from 1987 to 2015, while the area of study was the municipality of Poço Redondo, located in the northeast area of the state of Sergipe. In order to achieve this, anchored in the systemic approach of Geography and the presumptions of the landscape’s geoecology, multiple methodological procedures were applied, namely: literature review, documental research, production and analysis of cartographic products, with the use of remote sensing and geoprocessing techniques; as well as fieldwork for in situ analysis of the proposed desertification indicators. Thus, the analysis of the susceptibility to desertification was carried out through the integration of geoenvironmental indicators (vegetation index (NDVI) soil types, relief, pluviosity and land use), correlating anthropogenic derivations with support from geotechnologies in a multicriteria analysis. Such indicators subsidized the integrated analysis, providing mapping of the susceptibility to desertification, with regard to the geoenvironmental order of the studied municipality. As main results, it can be highlighted that the municipality has the following indexes of susceptibility: 4,7% very low; 9,7% low; 25,7% medium; 43,2% high and 16,4% very high while 0,4% corresponding to the water bodies. The significant predominance of hydraulic deficiency, in almost every month of the year, contributes to the susceptibility to the process of environmental degradation. A spatial correlation was observed between the precipitation levels, soils, topography, and the situation of the vegetation cover as levels of susceptibility to desertification. Moreover, it can be said that in the area of study, the main causes of degradation/desertification derive from inadequate land use, with practices of deforesting, overgrazing, over-cropping and salinization of irrigated areas, processes which turned the areas more susceptible to this kind of environmental degradation.